Unsur Al-Khafa' Di Dalam Nas Nas Syara' dan Kesannya Kepada Perkembangan Hukum Fiqh - Mohamad, Shukeri (Jurnal Usuluddin, 1996)
This article explains the meaning of al-Khafa' according to al-Qur'an and al-Sunah (especially in the orientation of Usul Fiqh) and its impact on the legal judgement of fiqh. The existence of al-Khafa' in certain nas of syara' makes them not qat'ei in terms of dalalah (Its definition/Its legal judgement). This phenomenon broadens the meaning of ijtihad as to determine its accurate meaning and simultaneously spread the legal judgement of fiqh. In short, nas-nas of syara' consist of dynamic element which is essential in developing the legal judgement offiqh. However, when there is a stagnation in the use of nas-nas of syara', the dynamic element serves as an experimental object only.